Penentuan Prioritas Produk Unggulan Usaha Kecil Mikro Sektor Industri Agro Di Kabupaten Sukoharjo - Wardani, Irma; Dewi, Tria Rosana (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Regional superior products have high economic value and competitiveness, and absorb a large number of workers, which are produced with technical feasibility, community and institutional talent. The formation of superior MSME products in the Agro industry sector will contribute to regional development and economy. This research aims to determine priority factors for developing micro and small businesses and selecting priorities for micro, small and medium scale industries. The data used in this research are data from questionnaires and interviews. The tools used in the research are the AHP (Analytical Hierarchy Process) and MPE (Exponential Research Method) methods. The research results show that the criteria for superior products in Sukoharjo Regency are economic contribution, regional economic base sectors, market availability, facilities and infrastructure and technology. The priority superior product values ​​in Sukoharjo Regency are herbal medicine UKM (370,983,664), mushroom UKM (370,983,664), rattan UKM (241,967,328). The priority superior products to be developed are superior products from herbal medicine SMEs. It is hoped that superior products from herbal medicine SMEs will be able to contribute to the economy of Sukoharjo Regency and be able to compete in the global market